Congenital unilateral amastia: An unusual yet unique presentation associated with breech delivery - James, Vinson; Rajan, Jincy (Indian Journal of Case Reports, 2020)
Absence of the breast tissue is the least frequent of all the congenital breast anomalies. Amastia can be unilateral or bilateral and may have a syndromic association. Isolated congenital unilateral amastia is a very rare condition that is often misdiagnosed as Poland syndrome. Poland syndrome is a disease more common among males and often associated with other limbs, chest wall, and other digits anomalies, which makes surgical correction more tedious. Unilateral amastia in the absence of other anomalies may have a different etiology, and hence, it is worthwhile to explore other causes for the same. Herein, we present a rare case of a newborn with congenital unilateral right-sided amastia born through cesarean section in view of breech presentation.